Polycythemia in transgenic mice expressing the human erythropoietin gene. - Semenza, G L (1989)
Erythropoietin is a glycoprotein hormone that regulates mammalian erythropoiesis. To study the expression of the human erythropoietin gene, EPO, 4 kilobases of DNA encompassing the gene with 0.4 kilobase of 5' flanking sequence and 0.7 kilobase of 3' flanking sequence was microinjected into fertilized mouse eggs. Transgenic mice were generated that are polycythemic, with increased erythrocytic indices in peripheral blood, increased numbers of erythroid precursors in hematopoietic tissue, and increased serum erythropoietin levels. Transgenic homozygotes show a greater degree of polycythemia than do heterozygotes as well as striking extramedullary erythropoiesis. Human erythropoietin RNA was found not only in fetal liver, adult liver, and kidney but also in all other transgenic tissues analyzed. Anemia induced increased human erythropoietin RNA levels in liver but not kidney. These transgenic mice represent a unique model of polycythemia due to increased erythropoietin levels.